The Influence of the Role and Function of Patient Service Managers and Nurse Perceptions on the Implementation of Interprofessional Collaboration Healthcare Professionals in Dr. Iskak Tulungagung Hospital - Subekti, Dedi Eko; Indasah; Prasetyo, Joko (Universitas STRADA Indonesia, 2025)
Communication and collaboration that did not go well amounted to 66% with the most frequent cause being sentinel incident. Implementation of patient service management in dr. Iskak has been carried out since 2015. The purpose of this study is to analyze the influence of the role and function of the Patient Service Manager and the perception of nurses on the implementation of inter-professional collaboration at Dr. Iskak Tulungagung Hospital. The analytical research uses a cross-sectional approach. The research sample ware 120 nurses used simple random sampling. The research was carried out on July 1-31, 2024. The data analysis the Spearman Rho statistic with a value of Sig. (2-tailed) on the role factor of the patient service manager, namely p-value = 0.000 < 0.05, so Ho was rejected which means that the role factor of the patient service manager affects the implementation of inter-professional collaboration in Dr. Iskak Tulungagung Hospital.